In the Wake of the Great Recession: Economic Uncertainty, Communication, and Biological Stress Responses in Families. (15th October 2014) - Afifi, Tamara; Davis, Sharde; Merrill, Anne F.; Coveleski, Samantha; Denes, Amanda; Afifi, Walid
Abstract : The impact of spouses' communication about economic uncertainty on biological stress responses was examined. The sample included 82 Latino and Caucasian couples and one of their adolescents. Wives with low economic uncertainty experienced the greatest cortisol increase to a stressful discussion with their spouse, while wives with high economic uncertainty experienced a blunted cortisol response. Husbands with high economic uncertainty exhibited a low, unresponsive cortisol pattern. Wives who experienced elevated cortisol used more corumination and had low community support. The amount parents talked about their financial worries to their adolescent was not associated with the adolescent's mental health or biosocial markers, but the parents' economic uncertainty and corumination with each other were negatively associated with their own mental health .